Dispensing metformin with other drugs and dietary supplements in pharmaceutical care in patients with multimorbidity - Luiza Anna Żyrek; Lucyna Bułaś; Małgorzata Latocha (Polskie Towarzystwo Farmaceutyczne, 2023)
Pharmaceutical care is an activity aimed at protecting the patient's health. The purpose of this benefit is to provide assistance in receiving and safely using the drug. The idea of pharmaceutical care originated in the United States in the 70s' of the 20th century although the issue had already been discussed in the interwar period. The definition in force in Poland is contained in the Act on the Profession of Pharmacist (Act of September 10, 2020). The program includes pharmaceutical consultations, performing medications reviews, developing pharmaceutical care plans considering the patient's drug-related problems, performing diagnostic tests and issuing prescriptions that are a continuation of a medical order(1). This paper reviews the current literature on the use of metformin in patients with multimorbidity. Special attention was given to the studies on probability of occurrence potential drug-related problems in the treatment of these diseases. The analysis shows that the most difficulties are caused by the lack of knowledge about the treatment used by patients. The result is often a reduction in the regularity of therapy or even resignation from it. The obtained observations related to the combined use of drugs from different therapeutic groups should help to systematize knowledge about the current needs and expectations of patients. Properly conducted pharmaceutical care, including the preparation of drug reviews and education, can significantly improve the effectiveness of treatment. The article emphasizes the importance of the cooperation of the patient, doctor and pharmacist in achieving and maintaining the proper quality of life of the patient.